Identity-Based Encryption Secure against Selective Opening Chosen-Ciphertext Attack - Lai, Junzuo (Institutional Knowledge at Singapore Management University, 2014)
Security against selective opening attack (SOA) requires that in a multi-user setting, even if an adversary has access to all ciphertexts from users, and adaptively corrupts some fraction of the users by exposing not only their messages but also the random coins, the remaining unopened messages retain their privacy. Recently, Bellare, Waters and Yilek considered SOA-security in the identity-based setting, and presented the first identity-based encryption (IBE) schemes that are proven secure against selective opening chosen plaintext attack (SO-CPA). However, how to achieve SO-CCA security for IBE is still open. In this paper, we introduce a new primitive called extractable IBE and define its IND-ID-CCA security notion. We present a generic construction of SO-CCA secure IBE from an IND-ID-CCA secure extractable IBE with “One-Sided Public Openability”(1SPO), a collision-resistant hash function and a strengthened cross-authentication code. Finally, we propose two concrete constructions of extractable 1SPO-IBE schemes, resulting in the first simulation-based SO-CCA secure IBE schemes without random oracles.